1978
DOI: 10.1093/oxfordjournals.aje.a112568
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Dietary Methods in Epidemiologic Studies1

Abstract: Three methods of estimating group and individual dietary consumption have been developed and assessed in a case-control study of diet and breast cancer. The methods comprised a 24-hour recall, a detailed quantitative diet history directed to the most recent two-month period and the two-month period six months before, and a four-day diet diary. There is a high degree of correlation between the estimates of food consumption for the controls using each of the methods. The highest estimate was obtained from the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0
1

Year Published

1981
1981
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(71 citation statements)
references
References 0 publications
3
67
0
1
Order By: Relevance
“…The agreement was better at 8 than 18 months, re¯ecting the fact that by 18 months a more varied diet has been introduced. It is generally accepted that weighed intakes and duplicate diet collections tend to underestimate habitual intake, whereas the 24 h recall overestimates habitual intake (Morgan et al, 1978). Diet histories fall somewhere in between, and therefore give more representative estimates of nutrient intake, particularly for groups consuming a restricted variety of foods, as is the case with infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The agreement was better at 8 than 18 months, re¯ecting the fact that by 18 months a more varied diet has been introduced. It is generally accepted that weighed intakes and duplicate diet collections tend to underestimate habitual intake, whereas the 24 h recall overestimates habitual intake (Morgan et al, 1978). Diet histories fall somewhere in between, and therefore give more representative estimates of nutrient intake, particularly for groups consuming a restricted variety of foods, as is the case with infants.…”
Section: Discussionmentioning
confidence: 99%
“…The dietary intake of the infants was obtained from diet history data (Morgan et al, 1978) in which a standardised equation sheet was used by the interviewer (Table 1). This ful®lled the criteria listed by Marr (1971) in that it was comprised of an assessment of the overall pattern of eating, coupled with 24 h recall.…”
Section: Assessment Of Dietary Intakementioning
confidence: 99%
“…Using a cutoff value over 1.55 would lead to the exclusion of too many subjects, thus, to minimize bias we used the lowest cut-off that might reasonably exclude the major under-reporters, Using the same cut-off limit as in our study, Ballard-Barbash 22 reported higher levels of severe underreporting, which could be explained by his method of dietary assessment: four repeated 24 h recalls. Such 24 h recalls rely on memory and have been shown to give lower estimates of food intake than three-or four-day records, 30,31 leading to a higher proportion of underreporting. Using a seven-day weighed food record and the same methodology as us to identify underreporters in young adults, Haraldsdottir et al 25 found a similar frequency of underreporting, especially in men (18%).…”
Section: Discussionmentioning
confidence: 99%
“…Calculation of nutrient intake, overall glycaemic index and glycaemic load Data from the completed self-administered FFQs were used to estimate daily intake of nutrients using a database for Canadian foods that has been described elsewhere 25 . Data from the FFQ were also used to estimate overall GI and GL.…”
Section: Questionnairesmentioning
confidence: 99%